The effects of using BIM in detecting building design conflicts on architectural design products - Awder Omer Ali 1, a, *; Prof. Dr. Amjad Muhammed Ali Qaradaghi 2, a (Sulaimani Journal for Engineering Sciences)
The development of technology has always been a part of the design field over the last few centuries. The construction sector has recently begun to more efficiently integrate information technology into its design, building, and operations processes. Building Information Modeling (BIM) has emerged as a revolutionary technological approach in the field of architecture, offering integrated digital representations of building designs. This research paper investigates the effects of employing BIM in the detection of design conflicts within architectural projects. The study aims to explore how BIM technology enhances the identification and resolution of potential clashes between various building elements during the design phase, ultimately impacting the quality of architectural design products. The cases used in this research are limited only to low-rise residential complex buildings with an area ranging from 450-1000 m2 spread across Sulaymani city, designed between 2015-2022. The results of the study demonstrated that BIM is an effective tool for detecting clashes between architectural and mechanical elements. Additionally, clashes have a major impact on the five key aspects of architectural design products: function, space proportion, physical appearance, space shape, and exterior form.